LAPORAN KASUS: TYPHOID FEVER - Jihan Salma Azizah; Yunila Yunila; Wan Nendra (Cahaya Ilmu Bangsa Institute, 2025)
Typhoid fever is a systemic infectious disease caused by Salmonella enterica serotype Typhi, transmitted through the fecal-oral route. This disease has a high prevalence among children in developing countries, primarily due to poor sanitation and limited access to clean water. Typical symptoms in children include high fever, abdominal pain, nausea, vomiting, and diarrhea. Diagnosis of typhoid fever involves anamnesis, physical examination, as well as serological tests and culture. The primary therapy involves the use of antibiotics such as ceftriaxone, accompanied by supportive care. Prevention through vaccination and improved environmental hygiene is crucial in reducing the disease burden. Demam tifoid merupakan penyakit infeksi sistemik yang disebabkan oleh bakteri Salmonella enterica serotipe Typhi, yang ditularkan melalui rute fekal-oral. Penyakit ini memiliki prevalensi tinggi pada anak-anak di negara berkembang, terutama akibat sanitasi yang buruk dan kurangnya akses terhadap air bersih. Gejala khas pada anak meliputi demam tinggi, nyeri perut, mual, muntah, dan diare. Diagnosis demam tifoid dilakukan melalui anamnesis, pemeriksaan fisik, serta uji serologi dan kultur. Terapi utama melibatkan penggunaan antibiotik seperti ceftriaxone, disertai pendekatan suportif. Pencegahan melalui vaksinasi dan peningkatan kebersihan lingkungan sangat penting untuk mengurangi beban penyakit ini.